Sorption of dispersed petroleum hydrocarbons by activated charcoals: Effects of oil dispersants - Ji, Haodong; Xie, Wenbo; Liu, Wen; Xiaona Liu; Zhao, Dongye (Environmental Pollution, 2020)
Marine oil spill often causes contamination of drinking water sources in coastal areas. As the use of oil dispersants has become one of the main practices in remediation of oil spill, the effect of oil dispersants on the treatment effectiveness remains unexplored. Specifically, little is known on the removal of dispersed oil from contaminated water using conventional adsorbents. This study investigated sorption behavior of three prototype activated charcoals (ACs) of different particle sizes (4–12, 12–20 and 100 mesh) for removal of dispersed oil hydrocarbons, and effects of two model oil dispersants (Corexit EC9500A and Corexit EC9527A). The oil content was measured as n-alkanes, polycyclic aromatic hydrocarbons (PAHs), and total petroleum hydrocarbons (TPHs). Characterization results showed that the smallest AC (PAC100) offered the highest BET surface area of 889 m2/g and pore volume of 0.95 cm3/g (pHPZC = 6.1). Sorption kinetic data revealed that all three ACs can efficiently adsorb Corexit EC9500A and oil dispersed by the two dispersants (DWAO-I and DWAO-II), and the adsorption capacity followed the trend: PAC100 > GAC12 × 20 > GAC4 × 12. Sorption isotherms confirmed PAC100 showed the highest adsorption capacity for dispersed oil in DWAO-I with a Freundlich KF value of 10.90 mg/g∙(L/mg)1/n (n = 1.38). Furthermore, the presence of Corexit EC9500A showed two contrasting effects on the oil sorption, i.e., adsolubilization and solubilization depending on the dispersant concentration. Increasing solution pH from 6.0 to 9.0 and salinity from 2 to 8 wt% showed only modest effect on the sorption. The results are useful for effective treatment of dispersed oil in contaminated water and for understanding roles of oil dispersants.
Keywords: Activated carbon; Activated charcoal; Adsorption; Dispersed oil; Oil dispersant; Oil spill